Criteria of medical response to radiological emergencies in the Republic of Belarus - C. N. Buzdalkin; N. G. Vlasova; A. V. Rozhko; V. N. Bortnovsky (Радиационная гигиена)
The Republican Research Center for Radiation Medicine and Human Ecology in the Internal and External Emergency Plans of the Belarusian nuclear power plant is specified as an institution that provides specialized treatment for personnel, as well as persons from the population living in the emergency zone of the station. The plant is the first facility in the Republic that used nuclear energy. There is no experience in treating radiation injuries in Belarus. This is the first time that the National Health Service has been assigned the task of ensuring readiness for the reception and specialized treatment of people who have been exposed to emergency or unplanned radiation. The purpose of the work is to establish criteria for radiation exposure for use in a Belarusian specialized medical institution in case of medical response to radiological accidents. As a result of the analysis of publications of international organizations, the criteria of radiation exposure that can be applied in the conditions of Belarusian specialized medical institutions were selected. Assessment of the criteria was made taking into account existing national technical regulations and the available capabilities of emergency response participants. To account for the quality of radiation in relation to deterministic effects “Gy-equivalent” is used. The criteria include both dosimetric values for cases of external and internal accidental and unplanned exposure, and levels of radioactive substances with unknown physical and chemical properties entering the body that require urgent medical intervention. Criteria for cases of surface contamination of skin and wounds require separate consideration.